Continuous carbon fiber 3D printing with interweaving deposition for enhanced mechanical performance in fused filament fabrication - A. ElSherbiny; A.J. Qureshi; P. Mertiny (Additive Manufacturing Letters)
Additive manufacturing (AM) has revolutionized modern manufacturing by enabling the rapid prototyping and production of complex geometries with minimal material waste. Among AM techniques, Fused Filament Fabrication (FFF) is widely used for polymer-based manufacturing but exhibits limitations in high-performance applications due to insufficient mechanical properties. To address these shortcomings, this study focuses on advancing a standard FFF system to integrate Continuous Carbon Fiber (CCF) and implement interweaving deposition patterns, with the goal of enhancing structural performance and integrity. Representative volume element modeling and finite element analysis were conducted to evaluate the mechanical behavior, with results validated through experimental mechanical testing. The results confirm that CCF reinforcement improves the mechanical performance of printed components, particularly in the raster direction, although variations in response highlight the influence of material imperfections and non-linearities. The study demonstrates the potential of advanced CCF 3D printing in addressing the limitations of traditional FFF and provides insights for further advancements in polymer composite AM.